2016
DOI: 10.1002/aic.15574
|View full text |Cite
|
Sign up to set email alerts
|

A constitutive equation for thixotropic suspensions with yield stress by coarse‐graining a population balance model

Abstract: A population balance model appropriate for the shear flow of thixotropic colloidal suspensions with yield stress is derived and tested against experimental data on a model system available in the literature. Modifications are made to account for dynamic arrest at the onset of the yield stress, in addition to enforcing a minimum particle size below which breakage is not feasible. The resulting constitutive model also incorporates a structural based relaxation time, unlike existing phenomenological models that u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 66 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…1(d). There are many reports available in the literature, which confirm the above protocol for various thixotropic systems such as bentonite-water suspension [31], crude oil [32], fumed silica suspension [30,[33][34][35], carbon black suspension [36], Carbopol dispersion [37], human blood [38], theoretical models [39,40], which suggest this distinction to be useful. Recently Choi et al [41] discussed the role of elasticity during step down shear rate experiments using 2.9 vol % fumed silica suspension.…”
Section: Introductionmentioning
confidence: 69%
“…1(d). There are many reports available in the literature, which confirm the above protocol for various thixotropic systems such as bentonite-water suspension [31], crude oil [32], fumed silica suspension [30,[33][34][35], carbon black suspension [36], Carbopol dispersion [37], human blood [38], theoretical models [39,40], which suggest this distinction to be useful. Recently Choi et al [41] discussed the role of elasticity during step down shear rate experiments using 2.9 vol % fumed silica suspension.…”
Section: Introductionmentioning
confidence: 69%
“…μ s is the suspending medium viscosity, and η r is the relative suspension viscosity which depends on the volume fraction of particles in the suspension. Following Mwasame et al, 26 the medium viscosity term in the original Smoluchowski formulation of the aggregation kernel is replaced by the suspension viscosity to extend the applicability of the expression which was initially derived for dilute suspensions.…”
Section: Population Balance Model For Structural Thixotropymentioning
confidence: 99%
“…Foundational work by Mwasame et al 26 demonstrated that population balance modeling can be incorporated into a robust, efficient, and accurate rheological constitutive model. In that work, the model presented (hereafter referred to as PBEMono) used a monodisperse closure to develop the moment version of the population balance equation as a coarse-graining assumption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Population Balance Models (PBMs) take into account the flow-induced changes of the microstructure and describe how these changes influence the bulk rheology of the material. In the last years, there has been a growing interest in developing thixotropic constitutive models from PBMs [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%